PENGARUH FASILITAS BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA SWASTA TAMAN SISWA PEMATANGSIANTAR - Darazatin Husni; Anton Luvi Siahaan; Tumpal Manahara Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of learning facilities and interest in learning on the learning outcomes of class XI IPS students in the Economics subject at Tamansiswa Pematangsiantar Private High School. Based on observations, the learning facilities at this school are quite adequate, but student learning outcomes are still not optimal, with only 41.85% of students achieving scores above the Minimum Completeness Criteria (KKM) set at 78. This shows that there are other factors that influence learning outcomes, one of which is students' interest in learning which needs to be improved. The research method used is quantitative by collecting data through questionnaires distributed to students. Data analysis was carried out to test the hypothesis regarding the significant influence of learning facilities and learning interest on student learning outcomes. It is hoped that the results of this research can provide deeper insight into the factors that influence student learning outcomes and provide recommendations for improvements in the learning process at Tamansiswa Pematangsiantar Private High School. Thus, it is hoped that this research can contribute to efforts to improve the quality of education through developing learning facilities and increasing students' interest in learning.